Sanksi Tindak Pidana Pencantuman Klausula Baku pada Karcis Parkir Kendaraan Bermotor - Rizal, Moch. Choirul (al-Daulah: Jurnal Hukum dan Perundangan Islam, 2013)
Abstract: This article discusses about a criminal sanction of the standard clauses in a motor vehicle parking ticket for parking service manager according to article 18 paragraph (1) jo. article 62 paragraph (1) of Law No. 8 year 1999 about consumerâs protection. Standard clause is an agreement where the procedure of making it is unilateral. A standard clause listed on the ticket motorists has violated the provision of article 18 paragraph (1) letter a, namely âthe businesses doers, in offering goods and/or services that are held for trading, are prohibited from making or including a standard clauses in each document and/or agreement if they had declare the transfer of responsibility of entrepreneursâ. The inclusion of a standard clause as mentioned in the above provisions can be categorized as a criminal offense. The criminal penalty of such act isÂ  imprisonment of a maximum 5 (five) years or a criminal sanction of a maximum Rp. 2,000,000,000.00 (two billions rupiah) as stipulated in article 62 paragraph (1) UUPK. In Islam, these are included a criminal act and they have not stipulated in the text yet. So that, it becomes the authority of ulil amri to determine the punishment.Keywords: Sanctions, criminal act, standard clause, motor vehicle